Appropriateness Test of Training Module on Culturally-Competent Emergency Relief Foods (ERFs) for Disaster Prone Regions of India (Indian Journal of Extension Education, 2020)
A comprehensive knowledge on disaster prone regions of India and their culturally competent foods is crucial for nutritionists, extension specialists and other professionals involved in humanitarian assistance. A training module was developed for professionals who could use it while addressing the component of food assistance during emergency situations. The module complements the ongoing efforts of Indian government to address the food and nutritional needs of disaster hit evacuees of specific regions. Evaluation of the module for its content, presentation and applicability using an appropriateness scale was tested by a panel of 5 experts and 30 students in the year 2018-19. It was also assessed for its reading difficulty using Gunning Fog index. The results of the study showed that it was appropriate for its users and the reading difficulty index was also in line with the educational qualification of its intended users.